2022
DOI: 10.1186/s42269-022-00709-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and quercetin attenuated the reproductive toxicity mediated by lead acetate in male Wistar

Abstract: Background Heavy metals are well documented to induce reproductive toxicity. This study was designed to investigate the role of vitamin E and quercetin on reproductive toxicity mediated by lead acetate in male Wistar rats. Thirty male adult Wistar rats were grouped into six (n = 5 per group) as follows: Group 1 (Control); Group 2 and 3 were administered with 100 mg/kg vitamin E and quercetin, respectively; Group 4 was administered with 30 mg/kg lead acetate; Groups 5 and 6 received lead acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 52 publications
6
14
0
Order By: Relevance
“…The results of the current study are consistent with ( Oyeyemi et al , 2022 ), who reported that vitamin E could reduce testicular MDA and NO concentrations when co-administered with lead acetate due to suppress phospholipid membrane peroxidation and protect testicular cell membranes via its lipophilic properties ( Malmir et al , 2021 ); in addition, tocopherols-OH can replace their hydrogen atom to a single electron of free radicle and removing it before the free radicle binds with cell membranes, so vitamin E considers as a nonenzymatic defense mechanism in testicular mitochondria ( Ahmed et al , 2020 , Malmir et al , 2021 ) that effects on the testicular NO and MDA levels in Pb cotreated with vitamin E.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the current study are consistent with ( Oyeyemi et al , 2022 ), who reported that vitamin E could reduce testicular MDA and NO concentrations when co-administered with lead acetate due to suppress phospholipid membrane peroxidation and protect testicular cell membranes via its lipophilic properties ( Malmir et al , 2021 ); in addition, tocopherols-OH can replace their hydrogen atom to a single electron of free radicle and removing it before the free radicle binds with cell membranes, so vitamin E considers as a nonenzymatic defense mechanism in testicular mitochondria ( Ahmed et al , 2020 , Malmir et al , 2021 ) that effects on the testicular NO and MDA levels in Pb cotreated with vitamin E.…”
Section: Discussionsupporting
confidence: 91%
“…Lead ions can interfere with various cations, such as Mg +2 , Fe +2 , and Zn +2 , altering cellular pathway signaling and disturbing gene expression of enzymes and hormones ( Talpur et al , 2018 ). Furthermore, the hypothalamic-pituitary-testicular axis is the primary site of lead’s adverse effects on the male reproductive system, causing reduced sperm count, altered sperm maturation, and changes in sperm morphology that can result in infertility ( Li et al , 2018 , Oyeyemi et al , 2022 ). Lead exposure causes impairment in male reproductive function via apoptosis, testicular oxidative stress, and declined testicular antioxidants ( Wahab et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, QTN oral dosing significantly repaired the sperm-impaired parameters resulted from Al 2 O 3 NP s and PbAc co-exposure. Previous studies proposed that the positive effects of QTN on sperm characters could be partly related to its antioxidant activity [ 104 , 105 ]. Additionally, Taepongsorat et al [ 106 ] suggested that QTN might indirectly affect sperm quality via the stimulation of the sex organs (testis and accessory sex organs) at the cellular and organ levels.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study agreed with the studies (21,22) The reason for the high level of malondialdehyde is attributed to the effect of lead acetate on testicular tissues, which leads to lipid peroxidation in the cell membranes of the testicles. malondialdehyde Used as an indicator of cell membrane injury, the increase in the level of malondialdehyde in the testicular tissues increases lipid peroxidation and leads to tissue damage and the failure of antioxidant mechanisms to prevent the formation of free radicals (23).…”
Section: Resultsmentioning
confidence: 99%